On parliamentary war : partisan conflict and procedural change in the US Senate - Wallner, James I. (Legislative politics & policy making., 2017)
"Dysfunction in the contemporary Senate is driven by the deteriorating relationship between the majority and minority parties in the institution. In this environment, regular order is virtually non-existent and unorthodox parliamentary procedures are frequently needed to pass important legislation. This is because Democrats and Republicans are now fighting a parliamentary war in the Senate to help steer the future direction of the country. James Wallner presents a new, bargaining model of procedural change to better explain the persistence of the filibuster in the current polarized environment, and focuses on the dynamics ultimately responsible for the nature and direction of contested procedural change. Wallner's model explains why Senate majorities have historically tolerated the filibuster, even when it has been used to defeat their agenda, despite having the power to eliminate it unilaterally at any point. It also improves understanding of why the then-Democratic majority chose to depart from past practice when they utilized the nuclear option to eliminate the filibuster for one of President Barack Obama's judicial nominees in 2013. On Parliamentary War's game-theoretic approach provides a more accurate understanding of the relationship between partisan conflict and procedural change in the contemporary Senate"--Provided by publisher